The Role of Strategy Agility as a Mediation Variable is Reviewed with Human Capital and Absorptive Capacity in Influencing the Performance of PT Bank Sumut Kampung Lalang Branch Office - Rudi Ardi Anugrah Simbolon; Yeni Absah; Prihatin Lumbanraja (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the role of strategy agility as a mediating variable in the relationship between human capital, absorptive capacity, and performance of PT Bank Sumut Kampung Lalang Branch Office. The method used was a quantitative approach with data collection through questionnaires distributed to 49 respondents. The results of the study show that human capital and absorptive capacity have a positive and significant effect on company performance. In addition, human capital and absorptive capacity also have a positive effect on strategic agility. Strategy agility has been proven to be able to mediate the relationship between human capital and absorptive capacity to company performance. These findings emphasize the importance of human resource management and the organization's ability to absorb new knowledge to improve performance in the competitive banking industry. This research is expected to provide insight for management in formulating more effective strategies to improve the Company's performance.